The Political Economy Analysis of China–ASEAN in Service Industrial Cooperation and Open Policy. Issue 6 (1st November 2016) - Kung, Mei-Jan; Li, Ying-Zhen; Tai, Wan-Ping
Abstract : This study was divided into three parts. First, we compared and analyzed the competitiveness of trade in services and the degree of openness of the service sectors in China and THE five member states of the Association of Southeast Asian Nations (ASEAN), namely Singapore, Malaysia, the Philippines, Indonesia, and Thailand. Second, we empirically analyzed the panel data of the six countries. The empirical results indicated that China exhibited less competitiveness in trade in services and a lower degree of openness in the service sector compared with the other five countries. Furthermore, we determined that the competitiveness of trade in services was positively correlated with the openness of the service sector in the six countries. Third, we conclude by discussing and explaining the opening and collaboration of trade in services between China and ASEAN from political and economic perspectives.